Technical Efficency Of Soybean In Pandeglang Regency - Nivo Ardiansyah; Slamet Hartono; Any Suryantini (Agro Ekonomi, 2018)
Pandeglang district is the largest soybean producer region in Banten province. Since the last four years, Pandeglang Regency has decreased land area and production. However, the amount of soybean productivity has increased. The ability of farmers to manage and allocate various inputs used in soybean farming affects the production and productivity of soybean and can give an idea of the level of efficiency achieved by farmers. So it is necessary to research whether the application or use of inputs in the process of soybean production has been at technically efficient level or not. Based on these conditions, in this study aims to: know the level of technical efficiency in soybean farming in Pandeglang regency. The basic method used in this research is descriptive method and the location of research is determined intentionally or purposive sampling. Sample selection for soybean farmer respondents was done by simple random sampling method of 77 soybean farmers. The result of the research shows that production factors that significantly affecting soybean production in Pandeglang are wide, fertilizer and insecticide. The average value of farmers' technical efficiency is 0.864. This figure indicates that the average farmers of respondents have reached technical efficiency in soybean production in the research area. the technical efficiency value of the stochastic function with the lowest value 0.6314 and the highest value 0.9599. Factors affecting technical inefficiency are age and training. However, these factors have a positive effect, meaning that both increase the level of technical inefficiency of soybean farming.